Postherpetic Trigeminal Neuralgia of the V2 Branch Treated with Electrodes Placed through the Foramen Ovale: A Case Report - Cheng, Sitong; Zhang, Yue; Ou, Cehua; Li, Fubo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Varicella-zoster virus (VZV) is a deoxyribonucleic acid (DNA) virus that causes both primary and recurrent viral infections. Herpes zoster (HZ), also known as shingles, is a unique condition that is induced by VZV reactivation. Neuropathic pain, malaise, and sleep disruption are prodromal symptoms in such cases. Postherpetic trigeminal neuralgia is a neuropathic pain caused by VZV infection of the trigeminal ganglion or branches, which remains or reappears after herpes crusting. In this report, we present a case of post-herpetic trigeminal neuralgia of the V2 branch, exhibiting findings of unusual involvement of the trigeminal nerve. Notably, the patient was treated using electrodes placed through the foramen ovale.
Keywords: herpes zoster; trigeminal neuralgia; electrical stimulation; postherpetic neuralgia; pulsed radiofrequency